Legal regulation of the use of euthanasia: Foreign experience and Ukrainian realities - Tatiana Kulik; Tatiana Mironyuk (Юридичний часопис Національної академії внутрішніх справ, 2021)
The purpose of the study is to analyse the legal regulation of the use of euthanasia in foreign countries and to outline the prospects for the introduction of euthanasia in Ukraine. In the furtherance of this goal, it was necessary to perform the following tasks: to find out the content of the concept of euthanasia, to determine the constitutional basis for its introduction in foreign countries; to characterise the legal mechanisms for the introduction of euthanasia. The methodological basis of the research was a set of general scientific and special methods, and their complex application was aimed at achieving the goal and fulfilling the tasks of research. Constitutional and legal regulation of the use of euthanasia has also become the object of contemporary research in Ukraine. Defining in this paper is the comparative legal method, which allowed comparing approaches to the use of euthanasia in different countries. The forecasting determined the possible consequences of the use of euthanasia in Ukraine. Scientific originality consists in forming on the basis of studying the content of the concept of “euthanasia”, analysing and systematising the views of opponents and supporters of legalising euthanasia the position that the introduction of euthanasia is not a component of the right to life, but, on the contrary, is a violation of this right and denies the idea that human life is the highest social value. In the context of legal regulation of euthanasia, it should be clearly defined that the state encourages the termination of a person's life at will, and therefore departs from the postulate that a person's life is the highest value. The trend towards legalising euthanasia is observed in states with high living standards. It is probably related to circumstances that are outside the scope of legal science, so there is an urgent need to consider such processes by psychiatry, psychology, and sociology. In states that have legalised euthanasia, there are many problems, including cases of abuse by medical personnel, pressure from relatives of patients pursuing illegal interests, the relativity of doctors' conclusions about the condition of a sick person, and the inability to adequately assess what is happening to patients in serious condition. In connection with the above, the study suggests that legal regulation, including at the level of international legal standards, should address issues related to the use of artificial maintenance of human life, so there is a need to develop its procedure, conditions for application, start and termination. The issue of euthanasia as the termination of a person's life at their request due to illness, old age or due to a person's self-perception should be reviewed, and a number of states where it is legalised can already analyse the consequences of such a decision. It should also be borne in mind that the absolute inadmissibility of euthanasia in Ukraine does not solve issues related to the suffering of terminally ill people. Therefore, the study of this topic is important for Ukraine